Avaliação da fragmentação da paisagem no município de Serra (ES), visando a construção de cenários, utilizando modelagem dinâmica espacial e as métricas de paisagem - Batalha, Marta Leite Oliver (2023)
This research project was designed to obtain a doctor degree in Geography from the Postgraduate Program in Geography at the Federal University of Espírito Santo in accordance with the Dynamics of Territories and Nature research line. The object of this investigation is the municipality of Serra, located in the state of Espírito Santo, which was chosen because it is an integral part of the Greater Vitória Metropolitan Region. The methodology used is intrinsically linked to Landscape Ecology and Spatial Dynamic Modeling. In Serra, growth has been observed, driven by the installation of new industries, hospitals, subdivisions for high-end residences, and various service companies, including the encouragement of agritourism. This research aims to carry out an integrated study based on changes in land use and cover, through the application of the Land-use and Cover Change (LUCC) model, as well as the metrics generated by the Fragstats software, these being the methodologies used. Currently, as the Metropolitan Region of Vitória expands, the population seeks refuge and quality of life in rural spaces. These spaces, in turn, are often used as second homes for tourism and vacations, attracting both the local population and visitors. However, the influx of people can bring with it the implementation of new industries and industrial hubs, which requires a commitment to environmental preservation. It is essential that the environment is seen as a resource in need of conservation and restoration, especially in the face of continued urban growth. This research is based on the hypothesis that Landscape Ecology and Spatial Dynamic Modeling can provide a more accurate interpretation of landscape patterns, allowing the identification of impacts arising from land use and cover. It is believed that inadequate occupation of the landscape can threaten biodiversity, as well as ecosystem services. Based on the hypothesis elaborated, the central objective of this research used the Dinâmica EGO software, which made it possible to carry out essential modeling procedures; this included the calculation of use transition rates, the generation of transition probability maps and even spatial allocation. of these transitions with cellular automaton functions. Also, using LUCC, together with the use of Landscape Ecology and its metrics, it was possible to verify the dynamics of the landscape, its fragmentation, in the time frames of 1985, 1995, 2007, 2012 and 2022, as well as evaluate the effect of landscape heterogeneity, pointing to the possibility of ecological corridors, which provide connections between permanent preservation areas and existing conservation units. Finally, through simulation models of future landscapes, scenarios are presented over 50 years, in order to contribute to the decision-making of municipal managers and local entrepreneurs. As it is a municipality that has currently invested in agritourism, it is intended that the results of this research can contribute to existing management instruments, aiming to conserve natural resources for the maintenance of the biodiversity that remains